Analysis of Bertrand Russell's theological discussions in the Allameh Ja’fari's view - Hamedeh Rastaei; Abdullah Nasri (آموزه‌‌های فلسفه اسلامي, 2023)
The confrontation of Islamic philosophers with Western philosophers can be examined from different angles. Allameh Ja’fari pays a lot of attention to the opinions of Western thinkers; among these figures is Bertrand Russell, who has analyzed by Allameh Ja’fari through his intellectual personality and some of his opinions. In the beginning of his works, he quotes and criticizes some viewpoints of Russell. Russell's views on the supernatural, God, the order of the universe, the evil of the world, the purpose of creation, the role of God in the world, and the roots of the tendency towards God, are among the theological topics that Ja’fari has discussed and analyzed in his works. According to Ja’fari works, Russell expresses important points about the universe and its relationship with the supernatural, and on the other hand, about God, which indicates conflicts in his thought. Russell's misconception of God is the root of many of his illogical statements in some theological topics.